x → 1 lim x − 1 ∑ k = 1 1 0 0 x k − 1 0 0 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given function can be simplified to ( x − 1 ) 2 x 1 0 1 − 1 0 1 x + 1 0 0 . Since in the given limit the function assumes the form 0 0 , we apply L'Hospital's rule twice to obtain the limit as 2 1 0 1 × 1 0 0 = 5 0 5 0 .
Here's a non-L'Hôpital approach. If we rearrange the sum slightly, we can use direct algebraic division:
x → 1 lim x − 1 ∑ k = 1 1 0 0 x k − 1 0 0 = x → 1 lim x − 1 ∑ k = 1 1 0 0 ( x k − 1 ) = x → 1 lim ( 1 + ( x + 1 ) + ( x 2 + x + 1 ) + ⋯ + ( x 9 9 + ⋯ + x + 1 ) ) = 1 + 2 + 3 + ⋯ + 1 0 0 = 5 0 5 0
Problem Loading...
Note Loading...
Set Loading...
L = x → 1 lim x − 1 ∑ k = 1 1 0 0 − 1 = x → 1 lim x − 1 x + x 2 + x 3 + ⋯ + x 1 0 0 − 1 0 0 = x → 1 lim 1 1 + 2 x + 3 x 2 + ⋯ + 1 0 0 x 9 9 = 2 1 0 0 ( 1 0 1 ) = 5 0 5 0 A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x
Reference: L'Hôpital's rule